Improving the Snakebite Envenoming First Aid Treatment of Farmers in Rural Areas of Indonesia: An Educational Intervention Program (International Journal of Occupational Safety and Health, 2024)
Introduction: Snakebite Envenoming (SBE) cases are a worldwide health problem. Farmers have a big risk of becoming victims of SBE. SBE management is an issue that needs to be resolved due to a lack of information regarding the appropriate management of SBE. This study aimed to analyze the effectiveness of educational intervention programs on the knowledge, attitude, practice, and self-efficacy of farmers toward SBE management.Methods: The design of this study was a non-blinded cluster randomized controlled trial design, applied to 80 farmers in six subdistricts from rural areas of Indonesia. A multistage sampling was used to select participants. Data collection tools included a three-part questionnaire that consisted of demographics, knowledge, self-efficacy, and an observation checklist for SBE first aid practices for farmers. Education and training sessions were carried out for eight weeks for the intervention group by providing eight sessions of education and training activities. The effectiveness of the intervention was analyzed using a dependent t-test, and analysis of covariance (ANCOVA) with p